Inflammatory Response in the Anterior Chamber after Implantation of an Angle-Supported Lens in Phakic Myopic Eyes. (25th May 2014) - Taneri, Suphi; Oehler, Saskia; Heinz, Carsten
Abstract : Purpose . To evaluate the inflammatory reaction after implantation of an angle-supported foldable acrylic anterior chamber IOL for myopia correction over time. Methods . Adult individuals seeking vision correction with stable myopia >7.0 D were included. Exclusion criteria are anterior chamber depth <2.8 mm, insufficient endothelial cell density, other preexisting ocular conditions, and prior eye surgery. Laser flare photometry and slitlamp examination were performed before and up to 1 year after implantation of an AcrySof Cachet IOL (Alcon Laboratories, Forth Worth, TX, USA). Postoperative treatment comprised antibiotic eye-drops for 5 days and nonsteroidal anti-inflammatory eye-drops (NSAIDs) for 4 weeks. Results . Average laser flare values of 15 consecutive eyes of 15 patients were 8.3 ± 9.7 preoperatively and 19.0 ± 24.2 (1 day), 24.0 ± 27.5 (1 week), 17.6 ± 13.4 (1 month), 14.9 ± 15.4 (3 months), and 10.0 ± 7.0 (1 year) photon counts/ms after implantation, respectively. Slitlamp examination yielded 0 or 1+ cells (SUN classification) in every one eye throughout the follow-up period. Conclusion . Results indicate a low maximum inflammatory response and a quick recovery to a long-term safe level. The use of NSAIDs seems sufficient in routine cases, thus avoiding potential drawbacks of using corticoids.